Under the red flag : stories - Jin, Ha, 1956- (University of Georgia Press, 1997)
A collection of stories on the Cultural Revolution in China. In the story, A Man-to-Be, a soldier who refuses to participate in a gang rape pays the consequences, while In Broad Daylight, a woman is punished for being a prostitute.